Neomycin damage and regeneration of hair cells in both mechanoreceptor and electroreceptor lateral line organs of the larval Siberian sturgeon (Acipenser baerii). Issue 7 (23rd November 2015) - Fan, Chunxin; Zou, Sha; Wang, Jian; Zhang, Bo; Song, Jiakun
Abstract : The lateral line found in some amphibians and fishes has two distinctive classes of sensory organs: mechanoreceptors (neuromasts) and electroreceptors (ampullary organs). Hair cells in neuromasts can be damaged by aminoglycoside antibiotics and they will regenerate rapidly afterward. Aminoglycoside sensitivity and the capacity for regeneration have not been investigated in ampullary organs. We treated Siberian sturgeon ( Acipenser baerii ) larvae with neomycin and observed loss and regeneration of sensory hair cells in both organs by labeling with DASPEI and scanning electron microscopy (SEM). The numbers of sensory hair cells in both organs were reduced to the lowest levels at 6 hours posttreatment (hpt). New sensory hair cells began to appear at 12 hpt and were regenerated completely in 7 days. To reveal the possible mechanism for ampullary hair cell regeneration, we analyzed cell proliferation and the expression of neural placodal gene eya1 during regeneration. Both cell proliferation and eya1 expression were concentrated in peripheral mantle cells and both increased to the highest level at 12 hpt, which is consistent with the time course for regeneration of the ampullary hair cells. Furthermore, we used Texas Red‐conjugated gentamicin in an uptake assay following pretreatment with a cation channel blocker (amiloride) and found that entry of the antibiotic was suppressed in both organs. Together, our results indicate that ampullary hair cells in Siberian sturgeon larvae can be damaged by neomycin exposure and they can regenerate rapidly. We suggest that the mechanisms for aminoglycoside uptake and hair cell regeneration are conserved for mechanoreceptors and electroreceptors. J. Comp. Neurol. 524:1443–1456, 2016. © 2015 Wiley Periodicals, Inc. Abstract : Scanning electron micrographs illustrate that ampullary hair cells can be damaged by neomycin exposure, and the new ampullary hair cells regenerated completely in 7 days. This indicates that aminoglycoside sensitivity and the capacity for regeneration are conserved between electroreceptors and mechanoreceptors.